The istihalah (ةلاحتسا ) contention in gelatin issues and potential of halal gelatin alternative from gallus gallus domesticus using novel method - Halimah, Ab. Rahim (2021)
Fundamentally, a halal term for food is simple to understand as it refers to Shari’ah compliant in nature and sources, not originally haram or derives from haram sources. Nowadays, food preparation has no longer be simple but more complex with the introduction of ingredients and additives such as gelatin to improve the taste and look of food. The addition of gelatin has transformed food into a more resilient character. However, gelatin becomes controversial among Muslim consumers since more than 80% of gelatins are from a non-halal source, which is pork. Through Maqasid Shari’ah, the Ijtihad from Islamic jurists (ulama), Islamic scholars, and sects (Mazhab) regarding porcine gelatin have devided into two (2) points of view. Therefore, the first objective this study aims to clarify the Shari’ah views on Istihalah of gelatin comprehensively. The second objective aims to incorporate Islamic Law with the Science and Technology evidence, by conducting scientific methodology (experimental technique) through quantitative analysis. The alternative gelatin was proposed from Gallus gallus domesticus (chicken feet) that complied with critical control points (CCP) for halal poultry. The Halalan Toyyiban concept that covered the hygiene, safety, and quality aspect were inspected via physical and chemical properties of Gallus gallus domesticus (chicken feet) gelatin. Novel extraction methods that combined acid and alkali treatments were used to distrupt the homogenous tissues of Gallus gallus domesticus. The results for Gallus gallus domesticus gelatin quality for both treatments were comparable to commercial bovine gelatin. Overall, Gallus gallus domesticus gelatin meets the International Standard of Gelatin. The third objective aims to apply Gallus gallus domesticus gelatin in a new food product namely Kaya Slice. Kaya Slice was found to have more nutritious compared to commercial kaya. In conclusion, Gallus gallus domesticus has high potential to be an alternative to Halal gelatin. Keywords: Halal; Istihalah; gelatin; chicken feet; alternative.